Developing Automatic Test Assembly Using Lp-Solve and mySQL for Parallel Test Packages Based on the Information Function - Rumyati, R (Universitas Muhammadiyah Surakarta, 2015)
The purpose of this study is to develop item bank of mathematics based on IRT and an Automatic Test Assembly program (ATA) with some parameters that can be changed. The method used in this study refers to the Waterfall model suggested by Pressman. The developmental design was grouped into four developmental procedures consisting of: (1) Planning, (2) Modeling, (3) Construction, and (4) Deployment. The product assessment was carried out by a subject matter expert, psychometric expert, and IT expert through FGD. The unlimited scale of ATA trial and a larger scale trial respectively involved six and 15 teachers. The questionnaire was given to the experts and teachers. This study found two findings: (1) The item bank of mathematics for senior high school has been calibrated with IRT, and (2) The ATA program can assemble multiple parallel packages based on test information function (TIF) curve and content (competence standard, basic competence, and indicators).